Industrial Relations System as a Factor of Tripartite Consultation Influencing the Performance of State Corporations in Kenya - Nzioki, Susan; Mukulu, E. (International Journal of Advances in Management and Economics, 2013)
The study sought to establish the effect of Industrial relations system in Kenya on the performance of state corporations. Methodology: Data was obtained through a descriptive design involving 279 employees both unionized and non-unionized of state corporations in Nairobi County. A structured questionnaire with likert scale questions was used to collect data from the selected subjects of the study. Interviews were also conducted with human resource managers/ employee relations officers, shop floor union officials, officers of the Ministry of Labour, officers of Federation of Kenya Employers (FKE), officers of Central Organizations of Trade Unions, Kenya. The study used the Dunlop’s systems model credited with the application of the systems approach to Industrial Relations (IR). The model explains the input acquisition, input transformation, output and feedback to explain the process of Kenyan Industrial Relations System. Finding: The study found that there existed a prescribed Industrial Relations System in Kenya, but its adherence had been faced with a lot of challenges namely, reluctance to recognize trade unions, delay in conclusion of collective agreement, and partial implementation of collective agreements resulting to high rate of industrial actions in the country and delayed settlement of cases submitted to the industrial court. Besides, tripartite consultation as the study's intervening variable had intervened positively enhancing the performance of state corporations. Moreover, partnership approaches such as training, harmonization of partners' interests and high commitment had been experienced, translating to enhanced performance of organizations. Limitation: The study was concentrated in unionised state corporations and therefore cannot be generalized in the private sector and non unionised state corporations. Practical implications: provide evidence on the effect of the industrial relations system on tyhe performance of state corporations in Kenya and offer recommendations on what the three social partners and specifically the Kenya government needed to do to improve effectiveness of the industrial relations system in the country. Originality: This is the first study of this nature to be conducted in Nairobi County focusing on industrial relations system and intervention of tripartite consultation in the performance of state corporations.
Keywords: Industrial relations system, Kenya, Nairobi County, Social partners, Tripartite consultation.